Thermally stimulated cascade reaction polymer membranes: a promising strategy for an increased hydrogen and propylene purification performance. Issue 5 (26th October 2022) - Meis, David; Neumann, Silvio; Shishatskiy, Sergey; Meis, Ulrike; Filiz, Volkan
Abstract : A thermally stimulated cascade of reactions in solid-state of tailored polyimides was developed with the aim of lowering the target temperature for the final reaction step towards a polybenzoxazole and improvement of the gas separation performance. Abstract : Thermally stimulated solid-state reactions, forming polybenzoxazoles, from polyimides were reported about two decades ago, and introduced as promising membrane materials by Park et al. in 2007 Meanwhile most of the reported materials still suffer from low conversions at 400 °C and high TRonset temperatures, or low gas permeabilities, as a result of the increasing flexibility to compensate required annealing temperatures. In our study, we present a comprehensive structure–property–performance relationship, based on thermal-, film- and gas separation investigations, supported by molecular modelling and quantum mechanical simulations. Moreover, the execution of the TR process and other thermally triggered structure formations was performed within a molecular dynamics simulation for the first time. This was done in an amorphous cell and its properties, such as the free volume element characterisation with respect to a structure–property analysis done. Our materials provide among the lowest reported TR temperature and the lowest ever reported onset temperature (γE-PI) for a 6FDA-APAF based TRP and full conversion at 350 °C. βM-PI revealed 22% of TR conversion at an annealing temperature of only 300 °C and 84% at 350 °C, leading to several upper-bound performances, an efficient hydrogen and propylene purification performance, while having a good processability and a high chemical resistance, high TR conversion at low TRonset temperatures.